Dampak Aksi Boikot Produk Berafiliasi Israel Terhadap Pertumbuhan Produk Lokal di Era Konflik Israel-Palestina - Riyanti, Dini; Nisa, Fauzatul Laily (Diponegoro Journal of Islamic Economics and Business, 2023)
The Zionist-Hamas war peaked at the end of the year, and the two nations' struggle has greatly impacted every nation on the planet, particularly with regard to its economies. The boycott of Zionist products in support of Hamas in its fight for justice has created controversy in the economy of all countries, particularly in Indonesia. This boycott also affects local businessmen and entrepreneurs, as well as investors. This research discusses the boycott of products that support Zionist actions and how it affects local businesses. Using secondary data that the author processed, the descriptive qualitative approach method was used to analyze this study. The study's findings included a comparison of Zionist product sales before and after the boycott as well as sales of alternative Zionist goods, such as regional or non-Zionist goods.